2020
DOI: 10.1111/jav.02319
|View full text |Cite
|
Sign up to set email alerts
|

The importance of nighttime length to latitudinal variation in avian incubation attentiveness

Abstract: Avian incubation provides an opportunity to test how parental behavior and ecological conditions interact to shape variation in offspring traits along geographic gradients. In particular, the duration of the incubation period is shorter at higher latitudes, but the degree to which this pattern arises from genetic divergence in rates of growth and development versus from parentally‐mediated variation in egg temperatures is controversial. At higher latitudes parents have higher daytime incubation attentiveness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…This study is the first to quantify intraspecific variation in a suite of incubation behaviours (traits that trade‐off with other life‐history traits) along a large latitudinal gradient; incubation period duration, daily nest attentiveness and cumulative nest attendance were all positively correlated with latitude. Several studies have examined interspecific variation in these traits (Chalfoun & Martin, 2007; Martin et al., 2007; Martin & Schwabl, 2008), but few previous studies have reported intraspecific latitudinal variation in incubation behaviours (see Ardia et al., 2006; Sofaer et al., 2020) and none have compared populations at more than two study sites. The available intraspecific latitudinal comparisons of incubation periods are in species with intermittent incubation and reported results opposite of our patterns; both orange‐crowned warblers Leiothlypis celata and house wrens Troglodytes aedon had longer incubation periods at low‐latitude sites compared to high‐latitude sites (Dobbs et al., 2006; Sofaer et al., 2020; Tieleman et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study is the first to quantify intraspecific variation in a suite of incubation behaviours (traits that trade‐off with other life‐history traits) along a large latitudinal gradient; incubation period duration, daily nest attentiveness and cumulative nest attendance were all positively correlated with latitude. Several studies have examined interspecific variation in these traits (Chalfoun & Martin, 2007; Martin et al., 2007; Martin & Schwabl, 2008), but few previous studies have reported intraspecific latitudinal variation in incubation behaviours (see Ardia et al., 2006; Sofaer et al., 2020) and none have compared populations at more than two study sites. The available intraspecific latitudinal comparisons of incubation periods are in species with intermittent incubation and reported results opposite of our patterns; both orange‐crowned warblers Leiothlypis celata and house wrens Troglodytes aedon had longer incubation periods at low‐latitude sites compared to high‐latitude sites (Dobbs et al., 2006; Sofaer et al., 2020; Tieleman et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined interspecific variation in these traits (Chalfoun & Martin, 2007; Martin et al., 2007; Martin & Schwabl, 2008), but few previous studies have reported intraspecific latitudinal variation in incubation behaviours (see Ardia et al., 2006; Sofaer et al., 2020) and none have compared populations at more than two study sites. The available intraspecific latitudinal comparisons of incubation periods are in species with intermittent incubation and reported results opposite of our patterns; both orange‐crowned warblers Leiothlypis celata and house wrens Troglodytes aedon had longer incubation periods at low‐latitude sites compared to high‐latitude sites (Dobbs et al., 2006; Sofaer et al., 2020; Tieleman et al., 2006). Similarly, interspecific studies have documented longer incubation periods in tropical species compared to temperate species (Martin, 2002; Martin et al., 2007; Martin & Schwabl, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, a pressure to finish development early and/or allow for re-nesting after failure within a short breeding season might be a strong selection on fast development. Indeed, within-species studies demonstrated that northern populations have shorter incubation and nestling periods, faster growth and higher brood mass for the same age than southern populations [ 64 , 69 72 ]. Additionally, faster growth in northern temperate species can also be explained by the increased length of daytime during breeding period.…”
Section: Discussionmentioning
confidence: 99%